Gambaran HIV-AIDS Di Kota Kendari Tahun 2007 - David Niven Larira (Jurnal Keperawatan, 2014)
This research is aimed to identify the description of the victims of HIV-AIDS in the city of Kendari year 2007. the variable used in this research is HIV-AIDS. While the sub variable included in this research comprises of the knowledge, the means of infection and the prevention of HIV-AIDS, the neighborhood of victims before and after infectied by HIV-AIDS, the behavior of the victims before and after infectied by HIV-AIDS. The research informants consist of regular informants (ODHA and OHIDA), and key informant (Head of VCT HIV-AIDS). This type of research is descriptive qualitative, and the sampling method is purposive sampling, where there are 2 case of HIV and 3 cases of AIDS. The numbers of informants of the research are 6 people; 5 regular informants, and 1 key informant. The 5 regular informants consist of 4 men (1 ODHA) different places. Informants Zn was interviewed in a quite place, informant By was interviewed at Kendari Beach, informant Ry and Ru were respectively interviewed at a quite leased house, informant Fi interviewed at the Beach, and the key informant interviewed at canteen. The result of the interview from the 6 informants are then followed with data grouping according to each variables, and also making content analysis from each variables. The gained data is then manually processed by grouping the result of the interview basd on the purposes of the research. The result of the interview is analyzed (content analysis) and interpreted, and then presented in the from pf narration. The result of the research shows that the knowledge, behavior, neighborhood and the job of those infected by HIV-AIDS virus highly influences the chance of being infected by HIV virus. This is revealed after conducting a direct interview which shows that not all of the informants understand clearly what the HIV-AIDS is. Informants said that the spread of HIV-AIDS is through sexual relationship, blood, the liquid from vagina and cement, and from mother’ milk to their children. Some of the neighborhoods where the informants live do not mind to accept living with those infected, unless they will be discriminated from their neighborhoods. Some of those infected by HIV-AIDS used to work abroad, entrepreneur and house wife, and after the infection, some of them are discriminates. This is the consequence of the lack of knowledge about HIV-AIDS in the city of Kendari. Key Words : HIV-AIDS, Knowledge, Behavior, Neighborhoods, job